Kerjasama Indonesia dengan Australia dalam Menggali Potensi ICRI Sebagai Sumber Daya Laut - Regina Abigael Malik; H. M. Imran Hanafi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Indonesia is a country known for its richness in natural, diverse and beautiful marine resources. Coral Reefs are one of the ecosystems that must be protected and preserved as best as possible, so that they can become a place to live for marine animals such as fish and others. Australia's also a country known for its diverse and beautiful marine ecosystem. However, both countries are experiencing problems, namely that coral reefs are not maintained, so Humans overexploit coral reefs and cause fatal damage to coral reefs and other marine animals. ICRI, as one of the organizations that can maintain and preserve the sustainability of coral reefs, can be a bright spot for both of the countries to work together to maintain and protect marine ecosystems very well.